Peran Gembala Jiwa dalam Problematika Pernikahan Dini di Indonesia - F. Christa Natalia; Theresiani Bheka; Y. Wilson B.Lena Meo (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This article discusses the phenomenon of early marriage in Indonesia from the perspective of the Code of Canon Law, particularly Canon 1072, which emphasizes the pastoral duty of guiding young people away from premature marriages. Using a qualitative-descriptive method with a literature review approach, the study examines canonical texts, Church documents, and empirical data related to the issue. The findings reveal that Catholic marriage demands free and mature consent, emotional stability, and openness to the gift of life. Early marriage often fails to fulfill these essential elements, leading to negative social, psychological, health, and economic consequences. Furthermore, it highlights the challenges faced by the Church in pastoral accompaniment amid cultural and socioeconomic pressures that encourage early unions. Therefore, Canon 1072 remains a relevant and preventive pastoral guideline, aiming to protect the dignity and freedom of young people, promote responsible preparation for marriage, and strengthen the foundation of Catholic family life in modern Indonesian society.